Investigation on improving immunologic reconstitution insufficiency using DiwuYanggan capsules in AIDS patients - Ke, Jing Wen; Chen, Yao; Lei, En Ze; Xiao, Ming Zhong; Ni, Wei; Huang, Fang; Li, Han Min; Jiang, Hong Lin; Ruan, Lian Guo; Liu, Jian Zhong (Frontiers in Pharmacology, 2024)
Background: This study aimed to explore the mechanism of action of DiWuYangGan (DWYG) capsule in improving Immunological non-responder (INR) by analyzing the active ingredients of DWYG. Methods: The study employed a randomized, controlled, double-blind, single-simulation method. Patients were randomly divided into control and trial groups and treated with the primal highly effective antiretroviral therapy. To demonstrate the effect of DWYG on INR, patients in the control group were administered simulated DWYG, whereas patients in the trial group were administered DWYG capsules(ChiCTR1900024673). The chemical composition of DWYG was analyzed using ultra-performance liquid chromatography-high-resolution mass spectrometry. Potential targets of DWYG in the treatment of INR were identified and predicted using network pharmacology and molecular docking. The molecular mechanisms underlying the effects of DWYG were validated using a peripheral blood monocyte model. Results: The CD4:CD8 ratio in the trial group was significantly higher than that in the control group (P < 0.01). A total of 210 DWYG compounds were identified and network pharmacology revealed 182 potential therapeutic targets for DWYG and INR. The results of Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses showed that the toll-like receptor signaling pathway is one of the key pathways. This study demonstrated that DWYG reduced the expression level of TLR4 and the levels of IL-2, IL-10, and TNF-α, which are important cytokines involved in the immune response. Conclusion: The efficacy of DWYG in the treatment of INR confirmed the potential practical components of DWYG. Moreover, the results of network pharmacology and experimental validation showed that DWYG could restore the immune function of acquired immune deficiency syndrome patients by inhibiting the expression of TLR4 and related signaling pathways and the overactivation of immune function.